2020
DOI: 10.1080/15592294.2020.1853318
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to extracellular vesicles from Pseudomonas aeruginosa result in loss of DNA methylation at enhancer and DNase hypersensitive site regions in lung macrophages

Abstract: Various pathogens use differing strategies to evade host immune response including modulating the host’s epigenome. Here, we investigate if EVs secreted from P. aeruginosa alter DNA methylation in human lung macrophages, thereby potentially contributing to a dysfunctional innate immune response. Using a genome-wide DNA methylation approach, we demonstrate that P. aeruginosa EVs alter certain host cell DNA methylation patterns. We identified 1,185 differentially met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…involved in the proinflammatory response to infection [83]. More research has shown that trained immunity can be induced by non-specific stimuli, such as exposure to microbial components like OMVs [22,23]. OMVs also play a significant role in suppressing the host immune response in CF, where chronic bacterial infections are established in a thick mucus layer in the lungs overlying epithelial cells, limiting direct contact of the invading pathogens with host lung epithelia [85].…”
Section: Omvs Alter the Host Immune Response To Subsequent Bacterial ...mentioning
confidence: 99%
“…involved in the proinflammatory response to infection [83]. More research has shown that trained immunity can be induced by non-specific stimuli, such as exposure to microbial components like OMVs [22,23]. OMVs also play a significant role in suppressing the host immune response in CF, where chronic bacterial infections are established in a thick mucus layer in the lungs overlying epithelial cells, limiting direct contact of the invading pathogens with host lung epithelia [85].…”
Section: Omvs Alter the Host Immune Response To Subsequent Bacterial ...mentioning
confidence: 99%
“…This seems to be the first description of trans-kingdom regulatory activity of an sRNA contained in EVs. Likewise, in a genome-wide DNA methylation study, Kyung Lee and colleagues reported that EVs from P. aeruginosa can alter human lung macrophage methylation patterns by producing differential CpG methylation [ 74 ] and that some of the CpG affected was associated with cytokines, such as CSF3 [ 74 ]. These results indicate that the role of bacterial EVs and their cargo is more complex than previously thought.…”
Section: Physiological Roles Of Extracellular Vesiclesmentioning
confidence: 99%
“…P. aeruginosa OMVs causes dysregulation of the appropriate immune response to infection in macrophages by altering DNA methylation in human lung macrophages ( Kyung Lee et al., 2021 ). Epigenetic modifications alter the pattern of gene expression and have been reported to be important during the innate immune response, regulating B-cell fate and function and controlling T-cell differentiation and memory responses ( Lau et al., 2018 ; Zhang and Cao, 2019 ; Zhang and Good-Jacobson, 2019 ).…”
Section: Pseudomonas Aeruginosa (P Aeruginosa)mentioning
confidence: 99%